Not an "Ordinary Man": J. Gresham Machen and the Un-Queering of Evangelical Theology - Steelman, Austin (Religion and American culture, 2022)
In the 1920s, Princeton Seminary professor J. Gresham Machen was the leading fundamentalist intellectual of the Fundamentalist-Modernist controversy. His Calvinist theology, commitment to biblical inerrancy, and opposition to liberalism were passed on to and spread by his influential students including Carl McIntire, Harold Ockenga, and Francis Schaeffer. But in the early days of 1906, the young man who would go on to indelibly shape evangelical theology wrote home from Germany where he was a graduate student that he could never go into Christian ministry because of his "moral fault" that no "ordinary man" could understand. This article analyzes the coded language of J. Gresham Machen's letters during his pivotal personal crisis in the context of changing German understandings of "homosexuality" and Machen's lifelong homosocial tendencies. Moreover, it connects Machen's confrontation with his sexuality with his simultaneous confrontation with German liberal theology. In the fall of 1905, Machen found himself drawn to the more experiential and pluralistic Christianity of Wilhelm Herrmann. However, in facing his own perceived immorality, Machen found "Calvinism a very comforting doctrine indeed." He rejected modernism and spent his life defending a rigid orthodoxy against the theologies that would come to accommodate and embrace queerness. The results of his personal crisis echoed through the history of twentieth-century American evangelicalism. This article analyzes the historical process of "un-queering" theology that emanated from that crisis and demonstrates that resistance to queerness was woven into the ideological fabric of evangelicalism far earlier than scholars have yet recognized.